2018
DOI: 10.1098/rstb.2017.0440
|View full text |Cite
|
Sign up to set email alerts
|

Trophic rewilding as a climate change mitigation strategy?

Abstract: The loss of megafauna at the terminal Pleistocene has been linked to a wide range of Earth-system-level changes, such as altered greenhouse gas budgets, fire regimes and biome-level vegetation changes. Given these influences and feedbacks, might part of the solution for mitigating anthropogenic climate change lie in the restoration of extant megafauna to ecosystems? Here, we explore the potential role of trophic rewilding on Earth's climate system. We first provide a novel synthesis of the various ways that me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
122
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(133 citation statements)
references
References 97 publications
0
122
0
Order By: Relevance
“…Rewilding interventions may go beyond the above‐mentioned benefits and potentially contribute to human‐induced climate change mitigation strategies (Cromsigt, te Beest, et al., ; Olofsson & Post, ). In the Arctic for instance, thermophilic plants are expected to invade the tundra in a warmer climate and to grow faster and increase in abundance (Elmendorf, Henry, Hollister, Björk, Bjorkman, et al., ; Elmendorf, Henry, Hollister, Björk, Boulanger‐Lapointe, et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rewilding interventions may go beyond the above‐mentioned benefits and potentially contribute to human‐induced climate change mitigation strategies (Cromsigt, te Beest, et al., ; Olofsson & Post, ). In the Arctic for instance, thermophilic plants are expected to invade the tundra in a warmer climate and to grow faster and increase in abundance (Elmendorf, Henry, Hollister, Björk, Bjorkman, et al., ; Elmendorf, Henry, Hollister, Björk, Boulanger‐Lapointe, et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, Cromsigt, te Beest, et al. () concluded that rewilding should prioritize large non‐ruminant species since they have the greatest potential to address climate change drivers, including wildfire mitigation, while having the lowest methane emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Bussoni, Alvarez, Cubbage, Ferreira, & Picasso, ; Hoffman & Wiklund, ; Lemaire, Giroud, Bathily, Lecomte, & Corniaux, ). Replacing ruminants (such as bovids) with other herbivores (hind gut fermenters such as horses) can furthermore strongly reduce greenhouse gas emissions (Cromsigt et al, ). This could be especially relevant from a climate change perspective because ruminants are intensively used in livestock farming which contributes currently about 18% to the global warming effect (Steinfeld & Wassenaar, ).…”
Section: The Socio‐cultural and Economic Consequences Of The Analogoumentioning
confidence: 99%
“…Large herbivores can interact with climate change in a number of direct and indirect ways [40,41]. In the Arctic, caribou or reindeer (Rangifer tarandus) and muskoxen (Ovibos moschatus) are the only large herbivores.…”
Section: Can Trophic Rewilding Serve As a Climate Change Mitigation Smentioning
confidence: 99%